Role of poly(ADP‐ribose) polymerase activation in the pathogenesis of periodontitis in diabetes. (30th August 2017) - Adachi, Kei; Miyajima, Shin‐ichi; Nakamura, Nobuhisa; Miyabe, Megumi; Kobayashi, Yasuko; Nishikawa, Toru; Suzuki, Yuki; Kikuchi, Takeshi; Kobayashi, Shuichiro; Saiki, Tomokazu; Mizutani, Makoto; Ohno, Norikazu; et al.
Abstract: Aim: The aetiology of progressive periodontitis in diabetes has not yet been elucidated. We previously demonstrated that nitrosative stress is increased in diabetic rats with periodontitis. Nitrosative stress induces poly(ADP‐ribose) polymerase (PARP) activation. Here, we demonstrated the involvement of PARP activation in diabetic periodontitis and detailed the therapeutic effects of PARP inhibitor. Materials and Methods: Experimental periodontitis was induced by placing a nylon thread ligature. Half of the normal and diabetic rats received the PARP inhibitor, 1, 5‐isoquinolinediol, for 2 weeks. Gingival PARP activation was detected by immunostaining for poly(ADP‐ribose). Periodontitis was evaluated by gingival inflammatory cell infiltration, inflammatory gene expressions and micro‐CT analyses. Results: Although both periodontitis and the presence of diabetes increased PARP activation in the gingiva, diabetic rats with periodontitis had the highest activation of PARP. Diabetic rats with periodontitis also showed significant increases in monocyte/macrophage invasion into the gingiva, inflammatory gene expressions, nitrotyrosine‐positive cells in the gingiva and alveolar bone loss, all of which were suppressed by treatment with the PARP inhibitor. Conclusions: These results indicate the involvement of PARP activation in the pathogenesis and aggravation of periodontal disease in diabetes and suggest the therapeutic potential of PARP inhibition for treating periodontal disease, especially in patients with diabetes.